An Overview on Development of Membranes Incorporating Branched Macromolecules for Water Treatment. Issue 1 (2nd January 2023) - Ang, Wei Lun; Lau, Woei Jye; Tan, Yi Hong; Mahmoudi, Ebrahim; Mohammad, Abdul Wahab
ABSTRACT: Membrane technology has evolved to be one of the main filtration processes in various water/wastewater treatment applications. The success of the treatment process lies on the improved properties of membranes, notably water permeation, solute rejection, and antifouling capabilities. Over the past decade, hyperbranched macromolecules that comprise star polymers and dendrimers have gained increasing attention in membrane research as synthesis materials and modifying agents. These macromolecules which are composed of branched structure, high-density terminal functional groups, and large intramolecular free volume could offer an opportunity to design a new generation membrane with desirable characteristics. This review looks into the recent advances in the polymeric membrane synthesis and its modification using branched macromolecules. Highlights are given to the factors contributing to the changes in membrane properties (structural, morphological, and chemical functional groups) and performance after branched macromolecules are used as main membrane forming material or modifying agent. The review also discusses outlook and future works that can be further explored on utilizing branched macromolecules in membrane application. Challenges in promoting and commercializing branched macromolecules-based membranes are also discussed. This review can serve as a valuable reference for further development of membranes with improved performance and functionalities for water treatment application.